Cómo cazar un tigre (XXI Century. Spanish Literature and Culture, 2008)
Questioning the impenetrable barriers between literature and reality, in this article Juan Bonilla proposes a “therapeutic trip” through masterpieces that have made literature a trampoline to jump the conventions of reality, creating new worlds and maintaining afloat the possibilities of the human being to fantasize himself as being “something more than this. ”  Faced with a  writing that presents itself as a mere reflection of reality, the necessity of a literature that transforms us more into ¨Icarus¨ is established, anchored to the iron weight of the quotidian but always in search of the intangible and the unreal through our experience as a reader.
Keywords: literature; reality; fantasy; the experience of the reader